Pessoas desaparecidas: uma análise crítica sobre a política criminal do Estado - Carneiro, Eliana Faleiros Vendramini (2022)
Challenging the respect for human dignity, foundation of the Democratic State of Law, the disappearance of people still does not have the proper legal support. Symptomatically, although since 1916, Civil Law has taken care of the subject, its context has been merely patrimonial, ignoring the human victims. The concept of a missing person itself needs to be developed, in addition to the provisions of the recent Law n. 13.812/2019, in order to identify its various species and allow effective protocols for action, since the search is essential, in respect of that dignity, and, moreover, the life and physical integrity of the disappeared and all those interested in their encounter. The protected legal interests are, therefore, of the highest relevance, which, however, was not even able to generate the typification of forced disappearance. Disappearing, in other cases, does not have to be a crime, but, in an unprecedented way, requires an investigative search, which has been rejected as one of the main tasks of the civil police, it is believed that due to the lack of recognition of the gravity of the facts, of adequate instruments, especially digital, and personal training. Also in the police station, stereotypes about the disappeared and his/her family are reproduced, which urgently needs to be deconstructed, adding, in the present case, to humanized care, given the poignant pain suffered by the reporting victims. If the missing person is not found alive, the management of bodies and bones has also been a reason for criticism of the public power, which, without having a simple database, orders the bodies of the disappeared, already officially sought by family members, to be buried. Then it carelessly buries them and ends up incinerating bones, making the encounter never possible again. This history must be collectively remembered, to be modified, with a specific criminal policy to demonstrate the commitment of the public power to basic values of society